Meningkatkan Antusiasme Siswa melalui Metode Amtsal dalam Pembelajaran Fiqih Ibadah Umroh di MI Terpadu Baitul Makmur - Latifah Marfuatin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the increase in student enthusiasm in learning Fiqh in grade V students of MI Terpadu Baitul Makmur, totaling 38 people, through the application of the Amtsal method. This method is used to stimulate students' imagination through illustrations that are relevant to the material. The research approach used is a combination of qualitative and quantitative approaches in the form of Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. Data collection techniques include observation and interviews. The results of the study showed that the application of the Amtsal method in learning Fiqh significantly increased student enthusiasm. In addition, this method also helps students understand the material, including the pillars, the differences between hajj and umrah, and the procedures for carrying out the umrah pilgrimage. The high enthusiasm of students has a positive impact on increasing their understanding of the material being taught.